Techno-Economic Evaluation of Biological and Fluidised-Bed Based Methanation Process Chains for Grid-Ready Biomethane Production - Gantenbein, Andreas; Kröcher, Oliver; Biollaz, Serge M. A.; Schildhauer, Tilman J. (Frontiers in Energy Research, 2022)
Three different power-to-methane process chains with grid injection in two scales (1 MWel and 6 MWel) were analysed regarding their investment and operation cost. The process chains were based on biological or catalytic bubbling fluidised bed methanation in combination with proton exchange membrane or solid oxide electrolyser cells. A bottom-up techno-economic analysis showed a cost benefit of around 17–19% lower biomethane production cost for the bubbling fluidised bed technology as less than a third of the reactor volumes is required for catalytic methanation. This cost benefit is only given in combination with PEM electrolysis, as the high-temperature electrolyser stacks currently result in high investment cost. Based on electricity cost of 5 €-ct/kWhel and a plant size of 6 MWel, biomethane production cost of 13.95 €-ct./kWh for catalytic and 17.30 €-ct/kWh for biological methanation could be obtained, both including PEM electrolysis. A significant efficiency increase by integrating the heat of catalytic methanation reaction with the high-temperature electrolysis can be achieved; however investment cost have to decrease below 1000 €/kWel to obtain economically feasible production cost of biomethane. Under current economic and technological circumstances, CO2 methanation using the bubbling fluidised bed technology is the most cost effective.